Wrinkling and cracking atop elastic shape memory polymer - Sakinah Lokman (Nanyang Technological University, 2020)
Structural coloration can be achieved through the diffraction of light, if the surface of the material has submicron wavelength of visible light. Shape memory materials are materials that have the ability to return back to its original shape after being severely and quasi-plastically deformed. This is achievable when the right stimulus is being applied. One example of shape memory material is shape memory polymers. This project deals with commercially obtained Thermoplastic Polyurethane (TPU), which has a rubbery-like elasticity.